2009
DOI: 10.1007/s10722-009-9443-1
|View full text |Cite
|
Sign up to set email alerts
|

Genotypes and phenotypes of an ex situ Vitis vinifera ssp. sylvestris (Gmel.) Beger germplasm collection from the Upper Rhine Valley

Abstract: Wild grapevine Vitis vinifera ssp. sylvestris species are endangered in their natural habitats by modern landscape use and thus there is need of further collection and preservation of these species in ex situ collections or the preservation in situ. In this study 34 wild Vitis vinifera ssp. sylvestris accessions from the Upper Rhine Valley including a defined subpopulation are described and compared with six accessions from the former Yugoslavia stored in an ex situ collection. The accessions are described by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 29 publications
3
14
0
Order By: Relevance
“…Apparently many morphological parameters that are assessed in cultivar identification show unexpected plasticity possibly due to environmental influence or the age of plant tissue. Barth et al (2009) found similarly differences between the clustering based on microsatellite genotypes and phenotypes in a recent survey of another clonally propagated woody plant, Vitis vinifera ssp. sylvestris.…”
Section: Discussionmentioning
confidence: 76%
“…Apparently many morphological parameters that are assessed in cultivar identification show unexpected plasticity possibly due to environmental influence or the age of plant tissue. Barth et al (2009) found similarly differences between the clustering based on microsatellite genotypes and phenotypes in a recent survey of another clonally propagated woody plant, Vitis vinifera ssp. sylvestris.…”
Section: Discussionmentioning
confidence: 76%
“…When the analysis was implemented with other secondary descriptors, the ampelographic traits showed moderate variation. It has to be considered, however, that morphological parameters (especially those that refer to leaves) are influenced by environmental conditions and the age of the tissues, and this could determine phenotypic variation, also without genetic diversity (Barth et al, 2009). In order to restrict this aspect, the ampelographic data have been collected by the same operators and on the same plants under similar cultural condition.…”
Section: Discussionmentioning
confidence: 99%
“…The Précis d'Ampélographie Pratique by Galet (1952) can be considered the reference manual in ampelography, and many of the descriptors described there have been adopted by international organizations (like IPGRI and OIV) for the official description of grape varieties and Vitis species. Although the use of molecular markers is recommended for grapevine identification, ampelography provides relevant morphological and agronomical information for characterization studies, breeding programs and conservation purposes (Barth et al 2009;García-Munoz et al 2011;Lamine et al 2014). Nevertheless, the use of diverse (but sometimes highly correlated) ampelographic descriptors comprising shoot, leaf, cluster and berry traits yield large datasets that need to be treated in a proper way.…”
Section: Introductionmentioning
confidence: 99%